Hematopoietic Stem Cell Transplantation in Mucopolysaccharidosis Type II: A Literature Review and Critical Analysis. (30th May 2018) - Barth, Anneliese L.; Horovitz, Dafne D. G.
Mucopolysaccharidosis II (MPS II—Hunter syndrome) is an X-linked lysosomal storage disorder caused by a deficiency in iduronate-2 sulfatase. Enzyme replacement therapy does not cross the blood–brain barrier (BBB), limiting the results in neurological forms of the disease. Another treatment option for MPS, hematopoietic stem cell transplantation (HSCT) has become the treatment of choice for the severe form of MPS I since it can preserve neurocognition when performed early in the course of the disease. Even though the intravenous therapy does not cross the BBB, it has become the recommended treatment for MPS II, and HSCT was not often indicated. In an attempt to understand why this treatment modality is rejected by most specialists as a treatment option for patients with Hunter syndrome, we sought to raise all HSCT cases already reported in the scientific literature. Databases used were Medline/PubMed, Lilacs/BVS Cochrane Library, DARE, SciELO, and SCOPUS. Different combinations of the terms "mucopolysaccharidosis II, " "Hunter syndrome, " "hematopoietic stem cell transplantation, " "bone marrow transplantation, " and "umbilical cord blood stem cell transplantation" were used. A total of 780 articles were found. After excluding redundant references and articles not related to the theme, 26 articles were included. A descriptive summary of each article is presented, and the main features are summed up. The clinical experience with HSCT in MPS II is small, and most of the available literature is outdated. The available data reveal poor patient selection criteria, varied conditioning regimens, distinct follow-up parameters, and post-HSCT outcomes of interest, making impossible to compare and generalize the results obtained. Recently, after the development of new conditioning protocols and techniques and the creation of bone marrow donor registries and umbilical cord banks, HSCT has become more secure and accessible. It seems now appropriate to reconsider HSCT as a treatment option for the neuronopathic form of MPS II.